FRI0719-HPR Self-assessment of quality of life of patients with rheumatic diseases and other chronic diseases in the iexpac project. (12th June 2018) - García-Vivar, M.L.; Cea-Calvo, L.; de Toro, J.; Pantoja, L.; Lerín, C.; García-Díaz, S.; Galindo, M.J.; Marín-Jiménez, I.; Fernández, S.; Mestre, Y.; Orozco-Beltrán, D.
Abstract : Background: Improving quality of life is a goal in the treatment of patients with rheumatic diseases. Objectives: In this work, we describe the self-assessment of quality of life made by patients with rheumatic diseases and with other chronic diseases through an anonymous survey in the context of a wider project on quality of care. Methods: In the context of a quality of care project, focused in the perceptions of chronic patients with health care in Spain (assessed with the IEXPAC scale ("Instrument to Evaluate the EXperience of PAtients with Chronic diseases", http://www.iemac.es/iexpac/), a survey was handed patients with 4 different profiles of chronic diseases needing care in at least two different levels (i.e. hospital clinic and primary care): A) Patients with rheumatic diseases (rheumatoid arthritis or spondyloarthritis) from hospital clinics, B) Inflammatory bowel disease (IBD) patients from hospital clinics, C) Patients with human immunodeficiency virus (HIV) infection from HIV units and D) Patients with diabetes mellitus (DM) plus cardiovascular or renal chronic disease from primary care or endocrinology clinics. Patients were handed the survey and completed the survey at home, returning it by pre-paid mail. As part of the survey, they completed the quality of life questionnaire EQ-5D-5L. Results: 2474 patients received the survey, 1618 (65.4%) returned it (359 with rheumatic disease [mean age 55 years, 63% women], 341 with IBD [mean age 47 years, 48% women], 467 with HIV infection [mean age 52 years, 27% women], 451 with DM [mean age 70 years, 32% women). Patients with rheumatic diseases more frequently described moderate or severe problems with mobility, self-care and usual activities and reported more pain (table 1). Patients with rheumatic disease and IBD more frequently reported anxiety or depression (table 1). Scores in the Visual Analogic Scale "Your Health Today" (from 0 worst health to 100 best health) were lower in patients with rheumatic diseases (mean score 61.9 [SD 19.5]) than in patients with IBD (68.8 [17.8]), HIV infection (73.3 [19.1]) or DM (67.0 [17.1]), all multiple comparison tests rheumatic disease versus other, p<0, 001). Conclusions: Self-evaluation by patients showed that quality of life of patients with rheumatic diseases (rheumatoid arthritis, spondyloarthritis) is worse that that of patients with IBD, HIV infection or DM. Improving quality of life is an essential goal to achieve in the care of patients with these rheumatic diseases. Acknowledgements: Funded by Merck Sharp & Dohme of Spain and endorsed by 4 patients associations (CONARTRITIS: patients with arthritis; ACCU: patients with Crohn's disease and ulcerative colitis; SEISIDA: AIDS multidiscipline group, FEDE: patients with diabetes mellitus). Disclosure of Interest: None declared